SERVICE QUALITY, CUSTOMER SATISFACTION, BRAND TRUST AND REPURCHASE INTENTION - Rendy Sumara; Lina Salim (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
Research objectives - The purpose of this study was to analyze the factors that affect the repurchase intention of Starbucks Coffee Forward Oakwood Jakarta consumers related to service quality (servqual), customer satisfaction and brand trust.Design/Methodology/Approach - The quantitative analysis method uses structural equation modeling (SEM) analysis with LISREL software version 8.80. Sampling was carried out for 4 months. Respondents who were selected as respondents had criteria as consumers who had visited and had made a one-time purchase at Starbucks Coffee Forward Oakwood Jakarta. The research instrument was a questionnaire and the respondents filled it directly on the google form.Findings - The proposed research model meets the Goodness of Fit (GOF) category. The factor that affects repurchase intention is servqual which is an important factor in increasing repurchase intention. Customer satisfaction mediates the influence of servqual and brand trust with repurchase intention.Research limitations - This study is limited to Starbucks Coffee Forward located in Oakwood Jakarta. In the future, research can be carried out on Starbucks Coffee Forward Oakwood in other areas such as those in Bali.Originality/value - This study raises customer satisfaction and repurchase intention depending on the brand trust that consumers have. The novelty of this study is the object of research, namely Starbucks Coffee Forward Oakwood Jakarta. This Starbucks has a characteristic that is different from other Starbucks